Analisis Kepuasan Pelayanan dan Faktor yang Mempengaruhi Keputusan Pelanggan untuk Memilih Smartphone Samsung di Jabodetabek Menggunakan Metode IPA dan Model Kano - v, Marsellinus Bachtiar; ., Cassidy (Metris: Jurnal Sains dan Teknologi, 2020)
Smartphones are one of the must-have devices for modern society today. With the high demand for smartphones lately, many companies are competing to produce smartphones that suit consumer needs. Indonesia is one of the developing countries where the growth rate of smartphone use can still increase so that many smartphone manufacturers sell their products to Indonesia. From this phenomenon, researchers want to know the level of satisfaction of users of one of the leading smartphone brands in Indonesia and even in the world, namely Samsung. The purpose of this study is to determine what factors are considered good by customers and the company must maintain these services and what things are deemed not good and need to be improved again. This study uses the IPA method to determine the level of conformity between company services and customer expectations and the Kano model used to determine which services are included in the performance, basic, or delighter categories. From the results of these two methods can be integrated using the IPA-Kano integration table. Some things that still need to be improved from Samsung smartphones according to users who have filled out this questionnaire include good quality materials at a good selling price, attractive and modern product designs, product quality has a good price level, sufficient camera quality for purposes daily needs, and bonuses that make consumers satisfied.